HUBUNGAN PENGETAHUAN DAN SIKAP IBU HAMIL TENTANG ANTENATAL CARE DENGAN KUNJUNGAN K4: THE CORRELATION OF KNOWLEDGE AND ATTITUDES OF PREGNANT WOMEN ABOUT ANTENATAL CARE WITH K4 VISIT - Ratu Kusuma (Jurnal Psikologi Jambi, 2018)
INTRODUCTION The antenatal visit is an indicator that indicated to access to maternal health services and the compliance of pregnant women in checking their pregnancy to health workers. K4 coverage in Indonesia in 2016 was 85.35%, Jambi (58.06%) (strategic plan target:74.00%). In 2017 the lowest K4 coverage in Jambi City is the public health center Talang Bakung (88.08%) next to the public health center Paal Merah II (89.64%) with the provincial target (74.00%). This study aimed to determine the correlation of knowledge and attitudes of pregnant women about ANC with the K4 visit at the public health center Talang Bakung. METHOD Analytic descriptive research, populations were 30 pregnant women, used total sampling technique. Used demographic data instruments, knowledge instrument, attitude instrument and K4 visit instrument, with fisher exact test. RESULT The findings indicated that there is no significant correlation between knowledge and attitudes of pregnant women about ANC with the K4 visit with each p value p=0.678 and p=0.417. CONCLUSIONS AND RECOMENDATIONS It is concluded that knowledge and attitude of pregnant women about ANC did not affect to K4 visit to pregnant women. To the next researcher to research about ANC with a different method. Keywords: Knowledge, Attitude, ANC and K4 Visit